Genome‐Wide Association Study for Adaptation to Agronomic Plant Density: A Component of High Yield Potential in Spring Wheat. Issue 6 (1st November 2015) - Sukumaran, Sivakumar; Reynolds, Matthew P.; Lopes, Marta S.; Crossa, José
ABSTRACT: Previous research has shown that progress in genetic yield potential is associated with adaptation to agronomic planting density, though its genetic basis has not been addressed before. In the current study, a wheat ( Triticum aestivum L.) association mapping initiative (WAMI) panel of 287 elite lines was assessed for the effects of plant density on grain yield (YLD), 1000‐kernel weight (TKW), and grain number (GNO) in yield plots consisting of four evenly spaced rows. The YLD and GNO of inner (high plant density) rows compared with outer rows (low plant density) indicated a consistent pattern: genotypes that performed best under intense competition (inner rows) responded less to reduced competition (outer rows) while being generally the best performers on aggregate (inner plus outer rows). However, TKW was not affected by plant density. To identify the genetic loci, an adaptation to density index (ADi) was computed as the scaled difference in trait values between inner and outer rows. Results on biplot analysis indicated that ADi was correlated with YLD in high‐yielding environments, suggesting that it is a component of high yield potential. Genotyping of the WAMI panel was done through 90K Illumina Bead single nucleotide polymorphism (SNP) array. Association mapping employed using 18, 104 SNP markers for ADi identified a major locus in chromosome 3B at 71 cM that explained 11.4% variation in ADi for YLD and GNO. Functional marker for ADi will enable identification of the trait in early generations—not otherwise possible in spaced plants typical of pedigree breeding approach—and to select parents for hybrid development.